THE STAKEHOLDERS INFLUENCE ON RISK DISCLOSURE OF STATE-OWNED ENTERPRISES - Yeni Priatna Sari; Djoko Suhardjanto; Agung Nur Probohudono; Setyaningtyas Honggowati (Media Riset Akuntansi, Auditing & Informasi, 2023)
Abstract The objective of this paper is to examine the influence of the stakeholders on the risk disclosure of the state owned enterprises. Secondary data were sourced from the annual report of 14 sample state owned enterprises taken from the Indonesia Stock Market over 2010-2019 and the Indonesian Ministry of State Enterprises. Regression analysis was applied to test the stakeholders' influence on the state owned enterprises' disclosure. This research uses quantitative method and regression analysis to find that geographic diversification, leverage, and rating announcements issued by the rating agency significantly affect the risk disclosure of state-owned enterprises. This research contributes to the policy.